Improvement of 3R waste treatment creativity In basic education in Medan - Achmad, Nurman; Hasridani, Devin Defriza; Hadinugroho, Dwi Lindarto (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
One important resource at the level of basic education is human resources which requires increased self-competence complementing life skills interrupted by the main tasks as teaching educators. MIS Islamiyah Sunggal School, Medan with the foundation's social mission focuses on serving the average disadvantaged community around the school. The condition of such limited sources of funds requires an alternative way of creating an entrepreneurial spirit to increase income for school educators. For this purpose the 2019 USU TALENTA Community Service Team was conducted directly in the field with community involvement and university lecturers from the University of North Sumatra. The training is carried out with recycling activities and enhancing the 3R waste treatment creativity skills in basic education. It is expected to be able to overcome environmental pollution and open up new opportunities for the community to open up new jobs. In addition to overcoming environmental problems, it also advances the nation economically thereby reducing the number of unemployed people in this country.